Digital Social Media and English Writing Skills: Students’ Perceptions in an EFL Context - Muslimah, Ima (Majesty Journal, 2023)
Digital social media has become an increasingly important platform for language learning, particularly in supporting students’ English writing development. This study aims to investigate students’ perceptions of digital social media use in developing their English writing skills. The study employed a qualitative descriptive design involving 14 students from the English Education Department of Universitas Muhammadiyah Enrekang. Data were collected through an online questionnaire distributed using Google Forms. The questionnaire consisted of four sections: social media use, preference for short-form words, grammar use, and bilingual word use. The findings revealed that students had positive perceptions of digital social media as a supporting medium for English writing. Most students frequently used social media in their daily activities and for academic purposes. They also considered social media useful for accessing English content, communicating with others, and practicing written English. The results showed that 71.4% of students were aware of grammar use when writing on social media, while 92.9% stated that social media helped improve their grammar. However, students also reported several challenges, including the frequent use of short-form words, bilingual expressions, and grammatical errors that may influence formal essay writing. Overall, the study indicates that digital social media provides valuable opportunities for students to practice English writing, expand vocabulary, and develop grammar awareness. Nevertheless, students need guidance to use social media more critically and academically so that informal writing habits do not negatively affect formal English writing performance.